2016
DOI: 10.13168/agg.2016.0012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of PCC model dependent periodic signals in GLONASS position time series using Lomb_Scargle periodogram

Abstract: Exactly in November 2006 (GPS week 1400), the IGS analysis centers switched from using relative to absolute corrections. At the same time, also the EUREF analysis centers made this switch. Many research groups have evaluated the influence of the usage of relative PCC with respect to absolute PCC on the EPN site coordinates. The authors demonstrated the significant influences of the conversion from relative to absolute PCC. Maximum changes in height of about 30 mm occurred at some sites. The impact of switching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…If it is assumed (like Rebischung et al, 2011 andBaire et al, 2013) that obtained position component differences are statistically significant, if their satellites or with the number of orbital planes for GLONASS satellites (Meindl, 2011;Sidorov and Teferle, 2013;Dawidowicz and Krzan, 2016;Dawidowicz, 2018). The results obtained for the GLONASS-only solution (Fig.…”
Section: The Position Component Differences In Sub-daily Observation mentioning
confidence: 97%
“…If it is assumed (like Rebischung et al, 2011 andBaire et al, 2013) that obtained position component differences are statistically significant, if their satellites or with the number of orbital planes for GLONASS satellites (Meindl, 2011;Sidorov and Teferle, 2013;Dawidowicz and Krzan, 2016;Dawidowicz, 2018). The results obtained for the GLONASS-only solution (Fig.…”
Section: The Position Component Differences In Sub-daily Observation mentioning
confidence: 97%
“…Previous research on PCC models indicated that transitions from different types of correction models, e.g., from relative to absolute or from mean to individual, cause noticeable changes in the position components (Baire et al 2013;Dawidowicz and Krzan 2016). In this study, the influence of differences between PCC models derived using a robot (GEO++) and chamber (IGG) methods on GNSS-derived position time series is assessed.…”
Section: Pcc Model Comparisonmentioning
confidence: 99%
“…The phase centers of global navigation satellite system (GNSS) antennas (receivers and satellites) show biases that should be modeled for precise positioning applications [ 1 , 2 , 3 ]. The real antenna phase center is not fixed, but its location varies depending on the receiving signal’s direction and frequency.…”
Section: Introductionmentioning
confidence: 99%